PERMIAN PALEOCLIMATE DATA FROM FLUID INCLUSIONS IN HALITE - Benison K.C.; Goldstein R.H. (My University, 1999)
This study has yielded surface water paleotemperatures from primary fluid inclusions in mid Permian Nippewalla Group halite from western Kansas. A `cooling nucleation' method is used to generate vapor bubbles in originally all-liquid primary inclusions. Then, surface water paleotemperatures are obtained by measuring temperatures of homogenization to liquid. Homogenization temperatures ranged from 21°C to 50°C and are consistent along individual fluid inclusion assemblages, indicating that the fluid inclusions have not been altered by thermal reequilibration. Homogenization temperatures show a range of up to 26°C from base to top of individual cloudy chevron growth bands. Petrographic and fluid inclusion evidence indicate that no significant pressure correction is needed for the homogenization temperature data. We interpret these homogenization temperatures to represent shallow surface water paleotemperatures. The range in temperatures from base to top of single chevron bands may reflect daily temperatures variations. These Permian surface water temperatures fall within the same range as some modern evaporative surface waters, suggesting that this Permian environment may have been relatively similar to its modern counterparts. Shallow surface water temperatures in evaporative settings correspond closely to local air temperatures. Therefore, the Permian surface water temperatures determined in this study may be considered proxies for local Permian air temperatures.
Keywords: LACUSTRINE SEDIMENTS; EVAPORITES; NON-MARINE; NIPPEWALLA GROUP; HOMOGENIZATION TEMPERATURES